Planning Workshop: Building A Covid-19 Rapid Response & Agricultural-Foresight Department In Egypt: Overview of IFPRI activities with MPED and MALR on which the project will build on - Raouf, Mariam (2021)
The online start-up workshop presented the "Building a COVID-19 Rapid Response and Ag-Foresight Department in Egypt" project’s activities and future plans, including collaborative discussion and brainstorming with stakeholders on the most relevant issues and policies in the agricultural sector’s resilience during COVID-19.